Inhibition of patchouli oil for anaerobic digestion and enhancement in methane production using reverse membrane bioreactors. (December 2018) - Lukitawesa,; Safarudin, Ahmad; Millati, Ria; Taherzadeh, Mohammad J.; Niklasson, Claes
Abstract: Patchouli oil is an essential oil extracted from aromatic crop Pogostemon cablin and is widely used in perfumery industry, food industry, and/or even as medicine. The leaves have 4.6% oil that is extracted by steam, but remains an enormous amount of wastes containing ca 0.8% oil. Patchouli waste is an interesting substrate for methane production. However, the oil has been found to have antibacterial activity. The inhibition of patchouli oil on anaerobic digestion was investigated in this study under thermophilic conditions (55 °C). The patchouli oil showed antibacterial effect, where addition of 0.05, 0.5 and 5 g/L patchouli oil reduced biogas production by 16.2%, 27.2% and 100% respectively. As patchouli oil is a lipophilic compound, hydrophilic polyvinylidene difluoride (PVDF) membrane was used to protect the microorganisms against this inhibitor in a reverse membrane bioreactor (rMBR) system. The methane yield of fresh plant and waste were 86 and 179 NmL CH4 /gVS, respectively when using free cells. Although using solely an rMBR did not give significant rise to methane yield, the combination rMBR and free cell strategy to protect part of the digesting microorganisms against this inhibitor considerably enhanced the methane production by 73% for fresh patchouli plant, compared to digestion using free cells. Highlights: Patchouli oil is largely used in perfumery, food and beverage industries. Each kg patchouli oil leaves 38 kg lignocellulosic wastes containing the oil. Patchouli oil is a strong inhibitor in anaerobic digestion. Membrane bioreactor can protect the cells to enhance digestion of patchouli biomass.